Grandes empreendimentos e desenvolvimento local: proposição de modelo de avaliação do impacto da implantação do Polo Industrial e Tecnológico da Saúde, em Eusébio-CE, no desenvolvimento local sustentável da região - Souza, Juliana Bezerra de (2017)
Objective- This dissertation proposes a model to evaluate the impact of the implementation of the Polo Industrial e Tecnológico da Saúde (PITS), in Eusébio-CE, on development indicators of the affected area. Methodology- Two different approaches to estimate the impacts of the PITS are presented, both of which rely on comparisons between development indicators of the area directly affected with that of similar areas not affected by the enterprise. One consists of comparing the whole Fortaleza metropolitan region with a synthetic Fortaleza, which is constructed by weighing other metropolitan regions in the country. The second approach consists of comparing Human Development Units (UDH) in the immediate vicinity of PITS with that of similar UDHs, both in the Fortaleza metropolitan area and other metropolitan areas of the North and Northeast of the country. Results- The dissertation generated an impact evaluation model that can be characterized as ex-post and quantitative, and which can now be implemented in a relatively straightforward way once post-intervention data become available. Limitations- The dissertation consists only of the design of the impact evaluation. The actual evaluation will only be carried out once post-intervention data become available. Practical contributions- The dissertation generated an evaluation tool that can be implemented, in the future, by any interested party, such as local governments, academics or Fiocruz itself. Social contributions- If implemented, the impact evaluation can inform policymakers’ decisions. The dissertation can also help disseminate the notions of impact evaluation. Originality- The impact assessment of interventions and policies is still not widely disseminated among public entities. As such, the dissertation generates an innovative applied tool for policymakers.